Pengaruh Work-Family Conflict terhadap Komitmen Organisasi: Kepuasan Kerja Sebagai Variabel Mediasi - Giovanny Anggasta Buhali; Meily Margaretha (Jurnal Manajemen Maranatha, 2013)
Several studies have examined how work-family conflict affectorganizational commitment. The aim of the study was to test whether work-family conflict affect the commitment variable mediated by satisfaction. The study was conducted at Maranatha Christian University. Subjects were 30 employees at Maranatha Christian University. Method of data collection using questionnaires.Test validity, reliability, multiple regression. Multiple regression analysis was used to test the hypothesis. The results showed that the Work-family conflict negatively affects organizational commitment and job satisfaction positively influences organizational commitment.Keyword: work-family conflict, organizational commitment, job satisfaction